1993
DOI: 10.1080/00994480.1993.10748048
|View full text |Cite
|
Sign up to set email alerts
|

Luminance-Controlled Pupil Size Affects Landolt C Task Performance

Abstract: Subjects judged the orientation of a 2 min. gap Landolt C located at a distance of 2.4 m. The stimuli were presented in central vision on a CRT, at low to medium contrast. The effects of varying the spectrum and luminance of surround lighting were assessed on both pupil size (measured using infrared pupillometry during task performance) and task accuracy. The task display was protected from the surround lighting, so that its luminance and contrast could be varied independently of the changes in the surround li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 20 publications
2
35
0
Order By: Relevance
“…As an example, in one visual test subjects must identify the location of an open section in a circle (called a Landolt C) that is briefly shown on a computer monitor. Many of these studies have identified statistically significant differences in people's performance on these visual tests with changes in lighting (e.g., Berman et al, 1993Berman et al, ,1994NEMA, 1989); however, the relationship between performance in these visually demanding laboratory tests and performance in typical work (e.g., office work) remains unclear.…”
Section: Direct Impacts Of Indoor Environments On Human Performancementioning
confidence: 99%
See 1 more Smart Citation
“…As an example, in one visual test subjects must identify the location of an open section in a circle (called a Landolt C) that is briefly shown on a computer monitor. Many of these studies have identified statistically significant differences in people's performance on these visual tests with changes in lighting (e.g., Berman et al, 1993Berman et al, ,1994NEMA, 1989); however, the relationship between performance in these visually demanding laboratory tests and performance in typical work (e.g., office work) remains unclear.…”
Section: Direct Impacts Of Indoor Environments On Human Performancementioning
confidence: 99%
“…However, based on the published literature (Boray et al, 1989;Veitch et al, 1991;NEMA, 1989) there seems to be no strong or consistent scientific evidence of benefits of full spectrum lighting. Berman et al, (1993; have found that changes in the spectrum of light (with illuminance unchanged) influence both pupil size and performance in visual tests. They suggest that the smaller pupil size when light is rich in the blue-green portion of the spectrum reduced the adverse effects of optical aberrations.…”
Section: Direct Impacts Of Indoor Environments On Human Performancementioning
confidence: 99%
“…Krtilova and Matousek (1980), summarising studies of mental workload, visual acuity and visual comfort in relation to lamp type, stated that "statistical evaluation of control tests shows best result for daylight, Daylight fluorescent [CCT=6500K, probably a FSFL] and discharge RVLX lamps" (p. 231), although they provided no detailed data. Berman, Fein, Jewett, and Ashford (1993) compared the effects of varying spectral composition and luminance (photometric brightness) on the performance of the Landolt ring task by 18-45-year-old participants who experienced all luminous conditions. Variations in spectral composition were achieved by varying the combinations of fluorescent lamps that provided the light around the task (the surround), which was presented on a computer screen.…”
Section: Visual Performancementioning
confidence: 99%
“…44 The two SPD conditions were created by using either three red and one pink lamp, or, in the other condition, one green-blue lamp (the "scotopically enriched" lamp). Pupil size was smaller, and visual performance was greater, for the blue-green lamp than for the red/pink combination, which is consistent with the theory.…”
Section: -31mentioning
confidence: 99%